ISLAM DAN ETIKA BERMEDIA SOSIAL BAGI GENERASI MILENIAL: TELAAH SURAT AL-’ASR - Wiji Nurasih; Mhd. Rasidin; Doli Witro (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
This research was conducted with the aim of exploring the content of Al-Quran surah al-’Asr and contextualizing it in order to respond to phenomena in millennial generation that are increasingly inseparable from communication activities through digital technology (social media) especially gadgets. Carefully public relations and gadgets have changed many settings ranging from moral values, culture, mindset, and so forth. In addition to the various benefits, the existence of social media has also been a trigger for various social problems that are counter to peace. Against this background, in this study, the authors sought to examine the Surah al-’Asr, whose contents will be formulated to be guidelines for how smart in optimizing social media. This qualitative research will use the Al-Quran hermeneutic approach that was initiated by Fazlur Rahman, namely the double movement theory. This method emphasizes to find universal values ​​so that the results of interpretations are progressive and can be applied in various contexts of space and time. From this research, it was obtained that Surah al-’Asr, if contextualized, could be obtained from him three moral ideals as proposed by Rahman. If all three are embedded in the consciousness of every human being, then this can be a solution for world peace. In the context of social media efforts that can be done is to optimize it as efficiently and effectively as possible for good and usefulness and to convey all things that are not contrary to the truth and human values.